Kredītiestādes klientu izpētes tiesiskie aspekti. - Daugaviete, Dace (Latvijas Universitāte, 2018)
В данный момент, на конец 2017 года, в Латвии, в соответствии с переносом действующих требований IV Директивы ПЛСПППФТ, уже проведен ряд изменений в нормативных актах ЛР, однако, часть правил еще следует ввести, в магистерской работе изучены возможности обеспечения полного переноса требований IV Директивы ПЛСПППФТ, а также совершенствования норм нормативных актов ЛР в соответствии с рекомендациями Группы разработки финансовых мер борьбы с отмыванием денег (FATF). Целью магистерской работы является проанализировать обязанность одного из субъектов права – кредитного учреждения – осуществлять изучение клиента, в рамках работы детально рассматривая и анализируя правовые аспекты изучения клиента, содержащиеся в IV Директиве ПЛСПППФТ. Ключевые слова: IV Директива ПЛСПППФТ; Рекомендации FATF; кредитное учреждение; изучение клиентов; мероприятия по изучению клиента; упрощенное изучение клиента; углубленное изучение клиента; истинный выгодополучатель; фактический владелец; централизованный реестр фактических владельцев (истинных выгодополучателей); политически значимое лицо; риск ЛСПППФТ; управление риском ЛСПППФТ.

At present, as at the end of 2017, in Latvia, in accordance with the transposition of the IV AML/CTF Directive existing requirements, a number of changes have been made in the regulatory enactments of the Republic of Latvia, however, a part of the requirements should stillbe introduced, this Master's Thesis considers the possibilities to transpose the IV AML/CTF Directive requirements in full, as well as to improve the regulations of the regulatory enactments of the Republic of Latvia in accordance with the Financial Action Task Force (FATF) Recommendations. The purpose of the Master's Thesis is to analyze one of the subjects of law – a credit institution’s obligations to perform Customer Due Dilligence (CDD), in the scope of work analyzing and considering the legal aspects of CDD, contained in the IV AML/CTF Directive, in detail. Keywords: IV AML/CTF Directive; FATF Recommendations; Credit Institution; Customer Due Dilligence (CDD); Measures for Customer Due Dilligence; Simplified Customer Due Dilligence; Enhanced Customer Due Dilligence; Real Beneficial Owner; Actual Owner; Central Register of Actual Owners (Real Beneficial Owners); Politically Exposed Person; AML/TF Risk; AML/TF Risk Management.
Legal aspects of Customer due diligence in a credit institution.
Keywords: Juridiskā zinātne; IV AML/CTF Directive; FATF Recommendations; Customer Due Dilligence (CDD); entral Register of Actual Owners (Real Beneficial Owners); Politically Exposed Person